2013
DOI: 10.4103/0974-2077.110092
|View full text |Cite
|
Sign up to set email alerts
|

Single treatment with 100-microsecond alexandrite laser clears selected acquired melanocytic nevi in type IV asian facial skin

Abstract: Context:Small common acquired melanocytic nevi (AMNs) are common on Asian facial skin.Aims:To show that the 755 nm Alexandrite laser stacked at the 100-μs long-pulsed mode (μsAL) is an effective modality for the removal of selected AMNs.Settings and Design:This was a retrospective case series, followed up with a telephone interview.Materials and Methods:A retrospective analysis of all patients treated between January 2010 and April 2012 with the μsAL laser for small AMNs was conducted. Pre- and post-treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
3
3
1
Order By: Relevance
“…Fitzpatrick skin type IV 77, (86.5 %) was most common followed by type III 07, (7.9%), an d type V 05, (5.6%) among 89 subjects. Study observed that highest number of participants have Fitzpatrick skin type IV followed by skin type III & V. These findings are comparable with the similar study done by Bencini PL et al, 12 Zhou X et al, 13 Bansal C et al, 11 Wang ECE et al 15 and Eric F et al 17 Most common type of tattoo among study participants was Amateur tattoo 63 (70.8%) while professional was 26(29.2%). Present study found amateur tattoo more that profession tattoo among participants which is comparable with the findings of similar study done by Jones A et al, 18 Klimer et al, 19 Ferguson & August et al 20 and Werner et al 21 But this finding is not similar with the study done by Kirby & Alston et al 14 82 study participants (92.1%) had blue-black and rest were 7 had Red -green (7.9%).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Fitzpatrick skin type IV 77, (86.5 %) was most common followed by type III 07, (7.9%), an d type V 05, (5.6%) among 89 subjects. Study observed that highest number of participants have Fitzpatrick skin type IV followed by skin type III & V. These findings are comparable with the similar study done by Bencini PL et al, 12 Zhou X et al, 13 Bansal C et al, 11 Wang ECE et al 15 and Eric F et al 17 Most common type of tattoo among study participants was Amateur tattoo 63 (70.8%) while professional was 26(29.2%). Present study found amateur tattoo more that profession tattoo among participants which is comparable with the findings of similar study done by Jones A et al, 18 Klimer et al, 19 Ferguson & August et al 20 and Werner et al 21 But this finding is not similar with the study done by Kirby & Alston et al 14 82 study participants (92.1%) had blue-black and rest were 7 had Red -green (7.9%).…”
Section: Resultssupporting
confidence: 84%
“…Male to female ratio was found out to be 1:0.25. Study included males more than females in the study which is comparable with the study done by Bencini PL et al 12 but not comparable with study done by Asilian A et al, 7 Zawar VP et al, 10 Aurangabadkar S et al, 16 Wang ECE et al 15 and Bansal C et al 11 where female participants were more than male participants.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Common acquired melanocytic nevi (AMNs) and small to medium-sized congenital melanocytic nevi (CMNs) are commonly treated with resurfacing laser devices, such as 10,600-nm carbon dioxide and 2,940-nm erbium:yttriumaluminum-garnet (YAG) lasers. [1][2][3] Lasers with selective photothermolysis are known to be effective against AMNs and CMNs by targeting the chromophores of melanin pigments in such lesions. Studies on pigmentspecific lasers in treatment of AMNs and CMNs have suggested that junctional nevus can be effectively treated with Q-switched pigment lasers and that longer-pulsed pigment lasers are effective in treating CMN.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on pigmentspecific lasers in treatment of AMNs and CMNs have suggested that junctional nevus can be effectively treated with Q-switched pigment lasers and that longer-pulsed pigment lasers are effective in treating CMN. [1][2][3][4][5] Wang et al 1 demonstrated that satisfactory treatment outcomes were achieved via a single session of 755-nm alexandrite laser treatment with a pulse duration of 100 μsec for small junctional nevus in Asian patients. Here, we report a case of darkly-pigmented and mammillated compound melanocytic nevus effectively treated by a 755nm alexandrite laser with a pulse duration of 3 msec.…”
Section: Introductionmentioning
confidence: 99%